Barriers to timely administration of birth dose vaccines in The Gambia, West Africa. Issue 29 (17th June 2016) - Miyahara, Reiko; Jasseh, Momodou; Gomez, Pierre; Shimakawa, Yusuke; Greenwood, Brian; Keita, Karamba; Ceesay, Samba; D'Alessandro, Umberto; Roca, Anna
Abstract: Objective: Although vaccine coverage in infants in sub-Saharan Africa is high, this is estimated at the age of 6–12 months. There is little information on the timely administration of birth dose vaccines. The objective of this study was to assess the timing of birth dose vaccines (hepatitis B, BCG and oral polio) and reasons for delayed administration in The Gambia. Methods: We used vaccination data from the Farafenni Health and Demographic Surveillance System (FHDSS) between 2004 and 2014. Coverage was calculated at birth (0–1 day), day 7, day 28, 6 months and 1 year of age. Logistic regression models were used to identify demographic and socio-economic variables associated with vaccination by day 7 in children born between 2011 and 2014. Results: Most of the 10, 851 children had received the first dose of hepatitis B virus (HBV) vaccine by the age of 6 months (93.1%). Nevertheless, only 1.1% of them were vaccinated at birth, 5.4% by day 7, and 58.4% by day 28. Vaccination by day 7 was associated with living in urban areas (West rural: adjusted OR (AOR) = 6.13, 95%CI: 3.20–11.75, east rural: AOR = 6.72, 95%CI: 3.66–12.33) and maternal education (senior-educations: AOR = 2.43, 95%CI: 1.17–5.06); and inversely associated with distance to vaccination delivery points (≧2 km: AOR = 0.41, 95%CI: 0.24–0.70), and Fula ethnicity (AOR = 0.60, 95%CI: 0.40–0.91). Conclusion: Vaccine coverage in The Gambia is high but infants are usually vaccinated after the neonatal period. Interventions to ensure the implementation of national vaccination policies are urgently needed.